Total Leukocyte Count And Platelet Count Are Related To TUBEX-TF Positivity Results In Typhoid Fever Patients At Dr. Pirngadi Hospital Medan City In 2018-2021 - Utami, Mega Diahsyah; Irma, Fani Ade (Universitas Muhammadiyah Sumatera Utara, 2025)
Abstract: Typhoid fever is a gastrointestinal infection caused by Sallmonellal typhi and Sallmonella serovar Paratyphi A (an important inhibitor of typhoid fever). Typhoid fever can be diagnosed based on clinical signs and symptoms, and laboratory tests. Leukopenia occurs due to the invasion of the bacterium Salmonella typhi into hematopoietic organs such as lymph nodes, tonsils, spleen, and bone marrow, thereby inhibiting hematopoiesis.The decrease in platelet production in the bone marrow is caused by viral infections, the destruction of platelet precursor cells in the bone marrow, radiation, aplastic bone marrow, bone marrow disorders or cancers, and other conditions that inhibit cell production in the bone marrow.This study aims to determine the relationship between total leukocyte count and platelet count in relation to Tubex-TF positivity in typhoid patients at RSUD dr. Pirngadi Medan from 2018 to 2021.This research uses an analytical observational method with a cross-sectional approach.The research sample consisted of typhoid patients at RSUD Dr. Pirngadi Medan from 2018-2021, which met the inclusion and exclusion criteria, totaling 71 patients.Analysis of the data was conducted using the chi-square test for both univariate and bivariate analyses.The total leukocyte count was found to be elevated in the case of a positive Tubex-TF in a patient with typhoid fever.